Pesticide Residues in Natural Products with Pharmaceutical Use: Occurrence, Analytical Advances and Perspectives - Pérez-Parada, Andrés; Colazzo, Marcos; Besil, Natalia; Dellacassa, Eduardo; Cesio, Verónica; Heinzen, Horacio; Fernández-Alba, Amadeo R. (IntechOpen, 2011)
None